Comparative study of drag and lift force for different shapes of submarines / Muhammad ‘Ammar Aiman Mohd Alif - Mohd Alif, Muhammad ‘Ammar Aiman (2022)
The optimal hydrodynamic form of a submarine's bow in terms of least resistance is discussed in this study. The hydrodynamic shape of submarines may be divided into two categories: the shape of a teardrop and a central body that is cylindrical. This study focuses on submarines with parallel (cylindrical) middle bodies because the bulk of naval submarines and ROVs have cylindrical middle bodies. Every hull has three parts: the bow, the cylinder, and the stern. This analysis does not include a conning tower (a sail)or any additional appendages. The goal of this work is to use the CFD approach and Flow Vision software to propose an optimal bow design. Resistance and the noise field (flow noise surrounding the sonar and acoustic sensors) are crucial elements in the hydrodynamic design of a military submarine's bow. The focus of this work is resistance in a fully immersed mode without free surface effects. The impact of these layout elements on the bow form is first investigated inside the bow of a navy submarine. Second, to better understand the foundations of bow design, examples of usage in historically significant naval submarines exhibit all possible shapes for submarine bow shapes. Finally, CFD analysis has been performed on all forms. These characteristics are constant in all models, except for the bow shape: diameter, stern form, and overall length; velocity, domain dimensions, and subsurface dimensions; (bow, middle and stern length)